2019
DOI: 10.1519/jpt.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Balance Evaluation of Prefrail and Frail Community-Dwelling Older Adults

Abstract: The BESTest seems to be more appropriate than a force plate for assessing postural control impairment and discriminating balance performance among frail, prefrail, and nonfrail older adults, providing information about different components of postural control rather than the force plate, which evaluates sensory orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Moreover, the aforementioned study group reported a higher prediction of frail and pre-frail status (Fried's criteria) under eyes closed conditions. In contrast, Marques et al 45 reported for 60 older adults who were divided into three groups of 20 (non-frail, pre-frail and frail), lower scores for frail in all sections and total score of the Balance Evaluation Systems Test (BESTest). At the same time, force plate measurements showed similar mean oscillation values in all three groups, indicating similar CoP behavior.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, the aforementioned study group reported a higher prediction of frail and pre-frail status (Fried's criteria) under eyes closed conditions. In contrast, Marques et al 45 reported for 60 older adults who were divided into three groups of 20 (non-frail, pre-frail and frail), lower scores for frail in all sections and total score of the Balance Evaluation Systems Test (BESTest). At the same time, force plate measurements showed similar mean oscillation values in all three groups, indicating similar CoP behavior.…”
Section: Discussionmentioning
confidence: 87%
“…At the same time, force plate measurements showed similar mean oscillation values in all three groups, indicating similar CoP behavior. 45 While in subjects using sensors attached to the lower back during a 25 m walk to analyze postural sway, Thiede et al 36 observed no significant differences in balance parameters based on the frailty phenotype of Fried 3 in 17 participants (≥55 years) with peripheral artery disease. 36 In contrast to the aforementioned studies, the patients in the study presented here were not only evaluated in relation to the frailty phenotype but, in addition, in terms of three other major frailty instruments, utilizing a different concept of frailty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, the balance might be impaired due to inability of the sensory system combined with muscle inefficiency to recover from perturbations on the COP placed by external forces ( e.g., gravity, body mass distribution, inertia) acting over stabilizing internal torques (mainly muscle and ligament forces). [ 52 , 53 ] As an example, decreased strength is related to diminished postural control, which is associated with increased risk of falls [ 53 ]. Impaired balance is also predictive of bad outcomes in older adults, such as frailty and higher prevalence of falls [ 14 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%